Go Digital! Empowering MSMEs in Kragan Village, Sidoarjo to Enhance Digital Marketing Skills - Karya, Denis Fidita; Mardhotillah, Rachma Rizqina; Anshori, Mohamad Yusak; Rihlah, Jauharotur (UKInstitute, 2025)
Digital transformation has become a critical need for Micro, Small, and Medium Enterprises (MSMEs), especially those in rural areas, to remain competitive in today’s market. This community service program was designed to enhance the digital marketing capabilities of MSMEs in Kragan Village, Gedangan Subdistrict, Sidoarjo Regency, East Java. The program was initiated in response to the low levels of digital literacy, limited access to online platforms, and the challenges MSMEs face in adapting to the evolving digital economy. Using a participatory approach, this initiative provided targeted training on social media marketing, e-commerce platforms, content creation, and basic digital tools such as WhatsApp Business and Canva. The methodology consisted of three phases: (1) problem identification and proposal submission, (2) implementation of workshops and hands-on mentoring, and (3) post-program evaluation through surveys and interviews. Results showed significant improvements in participants’ ability to utilize digital platforms, increased confidence in online business promotion, and a rise in customer engagement. Moreover, the training fostered knowledge sharing among MSME actors and strengthened their awareness of digital branding. The theoretical framework draws upon the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), highlighting how perceived usefulness and ease of use influence digital adoption. The program also applied the Community of Practice (CoP) approach to encourage peer learning and collaboration. This initiative demonstrates that with proper support and contextualized training, rural MSMEs can transition toward digital platforms effectively. The project also produced an Intellectual Property (IP) output in the form of training modules and digital marketing guides tailored for MSMEs. The findings call for ongoing mentorship, policy support, and infrastructure investment to ensure sustainability.